Biological reproduction of mackerel scad, Decapterus macarellus (Cuvier, 1833) caught by purse-seine net in Majene Waters, West Sulawesi, Indonesia - TENRIWARE TENRIWARE; MUHAMMAD NUR; ADIARA FIRDHITA ALAM NASYRAH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Tenriware, Nur M, Nasyrah AFA. 2023. Biological reproduction of mackerel scad, Decapterus macarellus (Cuvier, 1833) caught by purse-seine net in Majene Waters, West Sulawesi, Indonesia. Biodiversitas 24: 3012-3018. Mackerel scad, Decapterus macarellus Cuvier, 1833 is an economically important fish resource as an income source for fishermen in Majene waters, West Sulawesi. This study aims to determine some aspects of reproductive biology, including sex ratio, gonadal somatic index (GSI), gonad maturity stage (GMS), and the size at the first maturity. The sampling was carried out at the Fish Landing Sites in the Coastal Waters of Pangali-Ali Village, East Banggae District, Majene District, West Sulawesi Province, Indonesia. Each specimen was measured to the total length with digital calipers and body weight using a digital weighing scale. Initial sex assessment was noticed at the time of dissection, and gonadal maturity was also assessed. A total of 275 specimens consisting of 177 males and 98 females were obtained from April to July 2017. The result indicates that the sex ratio between males and females deviated from an expected 1:1: and was not balanced. This species spawns in April at the size of 173.4 mm and 168.6-178.3 mm for males and 189.1 mm or the range of 182.6-195.8 mm for females.